UJI IRITASI PADA KASUS PERIODONTITIS MODEL TIKUS WISTAR SETELAH APLIKASI EKSTRAK SARANG SEMUT - Lilies Anggarwati Astuti; Ika fikriah; Sinar yani (Lembaga Penelitian Universitas YARSI, 2024)
Introduction: Infected periodontal pocket by microorganisms plays an important role in the occurrence of periodontal tissue necrosis and the formation of periapical abnormalities. Therefore, periodontal pocket treatment should be carried out with the aim of eliminating or reducing the microbial population and biomechanically removing necrotic tissue which is a medium for microbial growth and preventing re-infection. One of the medicinal plants from the Kalimantan forest that has great potential is Sarang Semut (Myrmecodia pendens). (12) Objective: This study aims to determine the response of gingival healing in the case of periodontitis in the Wistar rat model after the application of Sarang Semut (Myrmecodia pendens) extract. Material and Methods: Sarang Semut (Myrmecodia pendens) extract dilution to concentration of 2.5%, 5% and 10% was carried. This research is a laboratory experimental research and used post-test with control group design. Results: There are three concentrations that have been given: 2.5%, 5%, and 10%. The smallest concentration provides a healing area. Discussion: The results showed that ethanol extract of Sarang Semut can increase the healing response of the gingiva that has been induced by periodontitis bacteria. Conclusion: Gingival healing response in periodontitis case of Wistar rat model after application of Sarang Semut extract (Myrmecodia pendens) showed results similar to positive control on 2.5% Sarang Semut extract application. Clinical signs on the rat's gingiva that experienced discoloration, countours and bleeding on the 3rd day gradually improved and on the 7th day there was no pocket depth.